THE INFLUENCE OF FINANCIAL LITERACY, PERSONAL SALES, AND CONSUMER TRUST ON PRIVATE HEALTH INSURANCE PRODUCT PURCHASE DECISIONS - Amalia, Egie; Arifin, Agus Zainul (Graduate Program of Universitas Tarumanagara, 2024)
The definition of risk in insurance is the uncertainty of future events that can cause financial losses. With health insurance, these risks can be managed so as not to cause financial losses. However, in general, Indonesian people have not placed health insurance as a priority to fulfill the need for security. The purpose of this study is to verify the relationship between Financial Literacy, Personal Selling and Consumer Trust on Purchasing Decisions with two theoretical approaches Theory of Planned Behavior and Social Exchange Theory. The data source used is primary data, which is obtained directly from respondents using an online questionnaire in the form of Google Form. The data collected was 521 data. The results of the study prove that Financial Literacy, Personal Selling, and Consumer Trust have a positive effect on Purchasing Decisions. The originality of this research is that it is the first attempt to evaluate private health insurance customers in Indonesia using the Theory of Planned Behavior and Social Exchange Theory approaches in parallel.